A coesão textual em livros didáticos do PNLD/2010: análise dos livros didáticos adotados pela Rede Pública Municipal de Barbacena - Elisabeth Goncalves de Souza (2012)
How is the textual cohesion approached in the didactic books adopted for students from the 3rd to 5th grades by the Municipal Public Schools in Barbacena (MG)? The purpose of this work is to answer this question, aiming the importance of the principle of textuality to reading and writing , departing from the analysis of 8 Portuguese didactic book collections, chosen by the municipal public teachers from the Programa Nacional do Livro didático (PNLD) 2010 - National Didactic book Program -.Thispaper offers contribution to the researches on the study of textual cohesion which, as it could be verified in the Capes portal, is still very incipient and dialogues with the most recently guidelines that direct the Portuguese teaching, especially the ones which aim to contribute to the formation of competent readers and writers, in a socialhistoricalperspective that considers the student as a subject of his /her educationprocess. We departed from a historical approach which rescues the Portuguese teaching trajectory and the analysis of the PNLD modifications since its creation in 1994 until the 2010 edition. We took as a theoretical basis the discussions of Textual Linguistics, especially the works by Beaugrande & Dressler (1981, 1997), Costa Val (1991, 1999, 2004), Marcuschi (1983, 1998, 2008), Koch (1988, 1996, 2000, 2002),Apotheloz (1995, 2003), Milner (2003), Cafiero (2002). In this thesis we tried to investigate if and how the didactic books analyzed contribute to lead the students to notice the importance of the cohesive elements to build the referential chain of the text.